Are Pakistan's women entrepreneurs being served by the microfinance sector? - Haq, Aban; Safavian, Mehnaz, 1970- (World Bank e-Library., 2013)
Financial services are important for women who are starting and growing a business, but in Pakistan microfinance providers (MFPs) are not reaching Pakistan's businesswomen. Only 59 percent of microfinance clients are women, yet the majority of these loans are passed on the male members of the household - husbands, fathers, and sons. The practice of passing on loans to male household members is quite widespread; women may be bearing all the transaction costs and risks of accessing loans, but are not the final beneficiaries. Second, a very low proportion of female microfinance clients are entrep.